1984
DOI: 10.1088/0741-3335/26/12b/012
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear electromagnetic wave transformation in a longitudinally magnetized plasma waveguide

Abstract: This paper deals with an experimental study of electromagnetic wave transformation in a longitudinally magnetized plasma waveguide (LMG plasma column). We have obtained the line averaged plasma density dependence with the incident power launched into the plasma. The results were carried out in argon. The paper presents evidence of anomalous absorption of an intense right hand circulary polarized wave (RHCP wave) at high magnetic fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…We stress that the electromagnetic wave excitation mechanism can hardly be due to a direct wave-wave coupling, since a wavenumber matching is not possible in any region of the interaction chamber, as the two waves have very different wavelengths. Further, higher order wave excitation based on echo-like phenomenology (BAKER andYONG. 1968 : YONG andBAKER, 1969) could hardly result in such a large amplitude EM wave.…”
Section: O N C L U S I O N Smentioning
confidence: 99%
See 2 more Smart Citations
“…We stress that the electromagnetic wave excitation mechanism can hardly be due to a direct wave-wave coupling, since a wavenumber matching is not possible in any region of the interaction chamber, as the two waves have very different wavelengths. Further, higher order wave excitation based on echo-like phenomenology (BAKER andYONG. 1968 : YONG andBAKER, 1969) could hardly result in such a large amplitude EM wave.…”
Section: O N C L U S I O N Smentioning
confidence: 99%
“…Further, higher order wave excitation based on echo-like phenomenology (BAKER andYONG. 1968 : YONG andBAKER, 1969) could hardly result in such a large amplitude EM wave.…”
Section: O N C L U S I O N Smentioning
confidence: 99%
See 1 more Smart Citation
“…7 The result is that, in this case, there may be some absorption of electromagnetic waves with LHCP polarization for magnetic fields that satisfy the condition (tJ = Wee' 8 The absorption in this case occurs via a two-stage process with two different thresholds, On the other hand, Kuckes 9 demonstrated that a RHCP wave is essentially completely absorbed under electron cyclotron resonance conditions. However, no systematic study has been made of the effectiveness of the absorption mechanism as a function of the polarization of the incident waves, taking into account the propagation theory of waves in cold plasmas which establishes, for these resonance conditions, a relation between the transformation of the waves and the collisional nature of the plasma.…”
Section: Introductionmentioning
confidence: 99%